Adsorption of LCFA on anaerobic sludge under steady state and shock loading conditions: effect on acetogenic and methanogenic activity - Pereira, M. A. (2002)
Accumulation of LCFA adsorbed onto the biomass was quantified under steady-state and shock conditions in a fixed bed reactor fed with oleic acid. The amount of adsorbed LCFA was more dependent on LCFA concentration than on LCFA loading rate and inhibited the acetogenic, acetoclastic and hydrogenophylic activity. However, even when methanogenic activity measurements indicate a severe inhibition, the anaerobic sludge was able to methanise adsorbed LCFA.